2022
DOI: 10.3390/molecules27134226
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles Using the Plant Extract of Acer oblongifolium and Study of Its Antibacterial and Antiproliferative Activity via Mathematical Approaches

Abstract: In this study, the antibacterial and antifungal properties of silver nanoparticles synthesized with the aqueous plant extract of Acer oblongifolium leaves were defined using a simplistic, environmentally friendly, reliable, and cost-effective method. The aqueous plant extract of Acer oblongifolium, which served as a capping and reducing agent, was used to biosynthesize silver nanoparticles. UV visible spectroscopy, X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Microorganisms are the most effective source for the synthesis of silver nanoparticles because their physiology and metabolism are already known. Moreover, microbial synthesis results in bulk production and less hazardous manufacturing processes [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms are the most effective source for the synthesis of silver nanoparticles because their physiology and metabolism are already known. Moreover, microbial synthesis results in bulk production and less hazardous manufacturing processes [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peak became sharper after 48 h which indicated complete synthesis of AgNP after 48 h of addition of AgNO 3 . In this context, Naveed et al have also observed synthesis of AgNP after 24–48 h at room temperature using the plant extract of Acer oblongifolium 21 . Information regarding physical state of photocatalytic NPs can be achieved by observing the SPR property.…”
Section: Resultsmentioning
confidence: 99%
“…Inorganic NPs, such as gold NPs, silver NPs, quantum dots, and carbon nanotubes, have a high molecular weight, and are hard in nature. The organic and inorganic NPs are biocompatible, non-toxic, and effective at delivering drugs to their intended targets [25]. Water pollution is one of the global challenges that society must address in the 21st century, aiming to improve water quality and to enhance health impacts of living beings.…”
Section: Discussionmentioning
confidence: 99%